Let-7e-5p Regulates IGF2BP2, and Induces Muscle Atrophy - Okamura, Takuro; Okada, Hiroshi; Hashimoto, Yoshitaka; Majima, Saori; Senmaru, Takafumi; Nakanishi, Naoko; Asano, Mai; Yamazaki, Masahiro; Hamaguchi, Masahide; Fukui, Michiaki (Frontiers in Endocrinology, 2021)
Background and Aims To understand the role of microRNAs in muscle atrophy caused by androgen-depletion, we performed microarray analysis of microRNA expression in the skeletal muscles of Sham, orchiectomized (ORX), and androgen-treated ORX mice. Methods To clarify role and mechanisms of let-7e-5p in the muscle, the effect of let-7e-5p overexpression or knockdown on the expression of myosin heavy chain, glucose uptake, and mitochondrial function was investigated in C2C12 myotube cells. Moreover, we examined serum let-7e-5p levels among male subjects with type 2 diabetes. Results We found that the expression of the miRNA, lethal (let)-7e-5p was significantly lower in ORX mice than that in Sham mice (p = 0.027); however, let-7e-5p expression in androgen-treated ORX mice was higher (p = 0.047). Suppression of let-7e-5p significantly upregulated the expression of myosin heavy chain, glucose uptake, and mitochondrial function. Real-time PCR revealed a possible regulation involving let-7e-5p and Igf2bp2 mRNA and protein in C2C12 cells. The serum let-7e-5p levels were significantly lower, which might be in compensation, in subjects with decreased muscle mass compared to subjects without decreased muscle mass. Let-7e-5p downregulates the expression of Igf2bp2 in myotube cells and inhibits the growth of the myosin heavy chain. Conclusions Based on our study, serum level of let-7e-5p may be used as a potential diagnostic marker for muscle atrophy.